2021
DOI: 10.1007/s00586-021-06818-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation in global treatment for subaxial cervical spine isolated unilateral facet fractures

Abstract: Purpose To determine the variation in the global treatment practices for subaxial unilateral cervical spine facet fractures based on surgeon experience, practice setting, and surgical subspecialty. Methods A survey was sent to 272 members of the AO Spine Subaxial Injury Classification System Validation Group worldwide. Questions surveyed surgeon preferences with regard to diagnostic work-up and treatment of fracture types F1–F3, according to the AO Spine S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…After screening titles, only ten articles were shortlisted for further review according to our selection criteria. Additionally, 26 articles were included by manual citation search to address our narrative review (4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening titles, only ten articles were shortlisted for further review according to our selection criteria. Additionally, 26 articles were included by manual citation search to address our narrative review (4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…While the latter system has demonstrated substantial inter-and intraobserver agreement, there is still inconsistency related to the terminology and interpretation of these injuries, which leads to a lack of standardization in the criteria related to the treatment of these injuries (8,31).…”
Section: Classificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 21 to 80% of these fractures failed to be treated only with non-operative management. 4 6 11) In a study by Spector and Vaccaro et al on unilateral facet fractures managed without surgery, it was found that 5 of the 24 patients later needed surgery due to either a shift in the fracture position or the onset of radiculopathy. Additionally, out of 6 patients who initially had radicular symptoms, 4 experienced no relief from their symptoms by the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Eine neuere retrospektive Kohortenanalyse an 39 Patienten konnte hingegen auch bei konservativer Therapie gute Erfolge vorweisen [57]. Auch im internationalen Vergleich ist die Versorgungsstrategie der F3-Verletzungen uneinheitlich [58].…”
Section: Operative Therapieunclassified